Effect of fruit dipping in sodium hypochlorite and oxalic acid then coating in bees-carnauba mixed wax on peel browning and decay of Vietnamese longan fruit - Le Ha Hai (2018)
The aim of this research was to evaluate the effect of sodium hypochlorite (SH) and oxalic acid (OA) dipping in combination with bees-carnauba mixed wax (MW) coating on decay and peel browning of Vietnamese longan fruit cv. Long. The experiments were firstly carried out by dipping fruits in 200 ppm SH solution for 2 min, and then dipping in 7.5% OA solution for 5 min. After drying in the shade, dipped fruits were coated in 4 and 6% MW for 30 seconds, and stored at 5±1°C for 30 days. Untreated fruits were used as control. Peel browning, peel color, polyphenol oxidase (PPO) activity, total microorganisms, percentage of fruit decay, fruit weight loss, and total soluble solids (TSS) content were monitored during the storage period. It was found that dipped fruits coated in 6% MW had delayed peel browning and fruit decay for 25 days in storage, and the TSS content remained unchanged. Moreover, the fruits maintained low PPO activity, low total microorganism levels and low weight loss. This result suggests that application of 200 ppm SH, 7.5% OA and 6% MW could be feasible for longan fruits storage on a commercial scale.